Guideline recommendations for diagnosis and clinical management of Ring14 syndrome—first report of an ad hoc task force - Rinaldi, Berardo; Vaisfeld, Alessandro; Amarri, Sergio; Baldo, Chiara; Gobbi, Giuseppe; Magini, Pamela; Melli, Erto; Neri, Giovanni; Novara, Francesca; Pippucci, Tommaso; Rizzi, Romana; Soresina, Annarosa; et al. (Orphanet journal of rare diseases, 2017)
Background Ring chromosome 14 syndrome is a rare chromosomal disorder characterized by early onset refractory epilepsy, intellectual disability, autism spectrum disorder and a number of diverse health issues. Results The aim of this work is to provide recommendations for the diagnosis and management of persons affected by ring chromosome 14 syndrome based on evidence from literature and experience of health professionals from different medical backgrounds who have followed for several years subjects affected by ring chromosome 14 syndrome. The literature search was performed in 2016. Original papers, meta-analyses, reviews, books and guidelines were reviewed and final recommendations were reached by consensus. Conclusion Conventional cytogenetics is the primary tool to identify a ring chromosome. Children with a terminal deletion of chromosome 14q ascertained by molecular karyotyping (CGH/SNP array) should be tested secondarily by conventional cytogenetics for the presence of a ring chromosome. Early diagnosis should be pursued in order to provide medical and social assistance by a multidisciplinary team. Clinical investigations, including neurophysiology for epilepsy, should be performed at the diagnosis and within the follow-up. Following the diagnosis, patients and relatives/caregivers should receive regular care for health and social issues. Epilepsy should be treated from the onset with anticonvulsive therapy. Likewise, feeding difficulties should be treated according to need. Nutritional assessment is recommended for all patients and nutritional support for malnourishment can include gastrostomy feeding in selected cases. Presence of autistic traits should be carefully evaluated. Many patients with ring chromosome 14 syndrome are nonverbal and thus maintaining their ability to communicate is always essential; every effort should be made to preserve their autonomy.